Multifocal Metastatic Breast Carcinoma to the Thyroid Gland Histologically Mimicking C Cell Lesions - Adeeba F. Ghias; Gregory Epps; Elizabeth Cottrill; Stacey K. Mardekian (Case Reports in Pathology)
The thyroid gland is an uncommon site of metastatic disease. Renal cell carcinoma is the most common primary source, while metastasis from breast carcinoma is very rare. However, given that thyroid nodules are more common in women, and women with a history of breast cancer are at higher risk of developing thyroid cancer, the possibility of metastatic breast carcinoma must be considered when evaluating a thyroid nodule. We present the case of a 67-year-old woman who presented with dysphonia and dysphagia secondary to multinodular goiter and was found to have multifocal metastatic breast carcinoma in her surgical resection specimen. The histologic appearance focally mimicked C cell hyperplasia and medullary thyroid carcinoma, so immunohistochemistry was critical for establishing the diagnosis. Metastasis to the thyroid should always be included in the differential diagnosis for a thyroid nodule in a patient with a history of previous malignancy.